Християнство як фактор формування духовної культури Київської Русі - Гудзенко-Александрук, Олена Георгіївна; Hudzenko-Aleksandruk, Olena H. (Полтавська державна аграрна академія, 2010)
У статті розглядається роль християнства у формуванні духовної культури Київської Русі. Відзначається, що запровадження християнства зробило можливим її долучення до досягнень світової культури. This article examines the role of Christianity in forming the spiritual culture of Kievan Rus. It is noted that the introduction of Christianity made it possible additions to the achievements of world culture.
Christianity as a Factor in the Formation Spiritual Culture of Kievan Rus
Keywords: духовна культура Київської Русі; духовні ідеали; еталони морального життя; загальнолюдські цінності; spiritual culture of Kievan Rus’; spiritual ideals; standards of moral life; human values